2010
DOI: 10.1530/eje-10-0376
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptors are down-regulated in skeletal muscle of patients with non-thyroidal illness syndrome secondary to non-septic shock

Abstract: Aim: Non-thyroidal illness syndrome (NTIS) is related to changes in thyroid hormone (TH) physiology. Skeletal muscle (SM) plays a major role in metabolism, and TH regulates SM phenotype and metabolism. We aimed to characterize the SM of non-septic shock NTIS patients in terms of: i) expression of genes and proteins involved in TH metabolism and actions; and ii) NFKB's pathway activation, a responsible factor for some of the phenotypic changes in NTIS. We also investigated whether the patient's serum can induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
(61 reference statements)
0
15
0
5
Order By: Relevance
“…Characteristic patterns of NTIS have been described in a multitude of acute and chronic somatic illnesses including states of shock (284), circulatory arrest (285, 286), respiratory failure (65), community-acquired pneumonia (287), sepsis (288), chronic respiratory (289, 290) and cardiovascular (61, 64, 66, 291, 292) disease, renal failure (293298), COPD (289), gastrointestinal diseases (299301), autoimmune diseases (71, 302, 303), and cancer (130, 290, 304). Phenotypes of NTIS with high and high-normal FT4 concentrations have been described in dementia and frailty in elderly persons (305).…”
Section: Thyroid Allostasis In Various Physiological and Pathologicalmentioning
confidence: 99%
“…Characteristic patterns of NTIS have been described in a multitude of acute and chronic somatic illnesses including states of shock (284), circulatory arrest (285, 286), respiratory failure (65), community-acquired pneumonia (287), sepsis (288), chronic respiratory (289, 290) and cardiovascular (61, 64, 66, 291, 292) disease, renal failure (293298), COPD (289), gastrointestinal diseases (299301), autoimmune diseases (71, 302, 303), and cancer (130, 290, 304). Phenotypes of NTIS with high and high-normal FT4 concentrations have been described in dementia and frailty in elderly persons (305).…”
Section: Thyroid Allostasis In Various Physiological and Pathologicalmentioning
confidence: 99%
“…patients, we showed that decreased THRB mRNA expression levels were associated with decreased protein level (Lado-Abeal et al 2010). MCT8 is so far the best-characterized TH transporter.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, desensitization has been suggested as a possible adaptation against exposure to excessive TH concentrations. For example, decreased TRa expression was reported in the heart of mice with myocardial infarction (29), as well as in skeletal muscle from patients with non-thyroidal illness syndrome (28). To the best of the authors' knowledge, this is the first study to evaluate TRb protein expression after acute versus chronic T3 treatment in vivo.…”
Section: Adaptations During Hyperthyroidism and Withdrawal 857mentioning
confidence: 89%